Edukasi Kosmetika Aman: Upaya Meningkatkan Pengetahuan Warga Gampong Kopelma Darussalam - Maryam, Siti; Isnaini, Nadia; Prajaputra, Vicky; Ulfa, Safra; Raihanylkhairi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The use of safe cosmetics has become an important concern among Indonesian society, especially with the rise of illegal cosmetic products containing hazardous materials such as mercury and hydroquinone. This community service activity aims to increase the knowledge of the Kopelma Darussalam Village community regarding safe cosmetics through education about the "Cek KLIK" method (Packaging, Label, Distribution Permit, Expiration). The methods used include socialization, distribution of educational brochures, and skin analysis using a skin analyzer. The results of this activity showed an increase in public understanding of cosmetic safety, as shown by the increase in post-test results compared to pre-test. The conclusion of this activity is that public education with interactive and practical methods has proven effective in increasing public awareness of the importance of safe cosmetics.